The history of initial teacher education in Canada: Québec and Ontario - Smyth, Elizabeth (2016)
This article traces the history of teacher education in Canada from the seventeenth century to the present by focusing on teacher education in the English-language dominant province of Ontario and the French-language dominant province of Québec. Because of the decentralized nature of education in Canada, it is at the provincial, not at the national level, where policies and practices for teacher education are developed and delivered. Like the history of Canada itself, the history of teacher education is marked by conflicts of gender, religion, power, class, race, language and ethnicity as teacher education struggled to claim a space itself in the academy and exercise its authority within the ivory tower. The article considers how the historical struggles and successes can both inform and cause us to critically reflect our current practice.